Promotion of Cortical Neurogenesis from the Neural Stem Cells in the Adult Mouse Subcallosal Zone. (19th January 2016) - Kim, Joo Yeon; Choi, Kyuhyun; Shaker, Mohammed R.; Lee, Ju-Hyun; Lee, Boram; Lee, Eunsoo; Park, Jae-Yong; Lim, Mi-Sun; Park, Chang-Hwan; Shin, Ki Soon; Kim, Hyun; Geum, Dongho; et al.
Abstract: Neurogenesis occurs spontaneously in the subventricular zone (SVZ) of the lateral ventricle in adult rodent brain, but it has long been debated whether there is sufficient adult neurogenesis in human SVZ. Subcallosal zone (SCZ), a posterior continuum of SVZ closely associated with posterior regions of cortical white matter, has also been reported to contain adult neural stem cells (aNSCs) in both rodents and humans. However, little is known whether SCZ-derived aNSC (SCZ-aNSCs) can produce cortical neurons following brain injury. We found that SCZ-aNSCs exhibited limited neuronal differentiation potential in culture and after transplantation in mice. Neuroblasts derived from SCZ initially migrated toward injured cortex regions following brain injury, but later exhibited apoptosis. Overexpression of anti-apoptotic bcl-xL in the SCZ by retroviral infection rescued neuroblasts from cell death in the injured cortex, but neuronal maturation was still limited, resulting in atrophy. In combination with Bcl-xL, infusion of brain-derived neurotropic factor rescued atrophy, and importantly, a subset of such SCZ-aNSCs differentiated and attained morphological and physiological characteristics of mature, excitatory neurons. These results suggest that the combination of anti-apoptotic and neurotrophic factors might enable the use of aNSCs derived from the SCZ in cortical neurogenesis for neural replacement therapy.